The Relationship between Burnout Occurrence and the Characteristics of Support Service Officers at Ciremai Hospital in 2025 - Nur Alifa, Seima; Haryanto, Yanto; Dewi Rahmawati, Fitria; Aryani, Bhakti (LPPM Universitas Dhyana Pura, 2025)
Burnout refers to a state of physical, psychological, and emotional fatigue that arises due to continuous workplace-related stress. This condition is frequently encountered among healthcare personnel, including those serving in hospital support roles. To assess burnout levels, several standardized tools are available, one of which is the Maslach Burnout Inventory (MBI). This instrument comprises 22 items categorized into three core aspects: emotional exhaustion, depersonalization, and diminished personal accomplishment. The objective of this research is to explore the association between burnout and demographic factors such as age, sex, marital status, educational attainment, and duration of employment. A quantitative approach using correlational analysis was employed in this study. The research involved total population sampling, encompassing 54 support service workers at Ciremai Hospital, with data collected through questionnaires. The data analysis process included both univariate and bivariate methods, with Spearman's rank correlation test utilized to evaluate inter-variable associations. Findings indicated that 33 respondents (82.5%) experienced moderate levels of burnout. Furthermore, statistical analysis revealed that among the five observed characteristics, only marital status showed a significant correlation with burnout (p-value = 0.040).